2020
DOI: 10.15372/rgg2020109
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Native Gold under Exogenous Conditions

Abstract: ––A long-term study of the typomorphism of native gold under exogenous conditions gave an insight into its evolution in time and space. The morphology, internal structure, and chemical composition of native gold change depending on the duration of its occurrence under near-surface conditions and on the thermodynamic parameters of the environment. Along with the known facts of gold transformation in the exogenous environment, we consider some of the first identified aspects of the evolution of native gold in we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…It has been revealed that such thick high-grade shells are characteristic of type I flake gold, which is very widespread in the east of the Siberian Platform. Thick high-grade shells (20-30 microns) on low-grade flake gold were found both in the northeast of the Siberian Platform in the basin of the Udzha river and in its central part in the Chebyda, Namana, Tonguo rivers and in its southern part in the basin of the middle Lena river (Figure 2d) [9,10]. The identified high-grade shells on gold particles with deformation lines are extremely rare (Figure 2e,f).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been revealed that such thick high-grade shells are characteristic of type I flake gold, which is very widespread in the east of the Siberian Platform. Thick high-grade shells (20-30 microns) on low-grade flake gold were found both in the northeast of the Siberian Platform in the basin of the Udzha river and in its central part in the Chebyda, Namana, Tonguo rivers and in its southern part in the basin of the middle Lena river (Figure 2d) [9,10]. The identified high-grade shells on gold particles with deformation lines are extremely rare (Figure 2e,f).…”
Section: Resultsmentioning
confidence: 99%
“…The internal structure of type II placer gold is practically unchanged, characterized mainly by mono-grain and coarse-medium-grained structures; sometimes, very thin highgrade shells are noted (Table 1; Figure 3). In addition, it has been found to contain unclearzonal and interblock structures, as well as a porous, spongy structure characteristic of gold from near-surface deposits, found at the mouth of the Bolshoi Patom river, indicating the proximity of the primary source [9,10]. The placer gold of the Mesozoic stage of ore formation is also characterized by granulation, disintegration structures (Figure 4а-c) and unclear-zonal structures (Figure 4d,e), found in the basin of the middle Lena, along with gold, whose internal structures are the structures of primary recrystallization and secondary recrystallization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations